2003
DOI: 10.1038/nsb952
|View full text |Cite
|
Sign up to set email alerts
|

A conserved amphipathic helix in WASP/Scar proteins is essential for activation of Arp2/3 complex

Abstract: Members of the Wiskott-Aldrich syndrome protein (WASP) family link Rho GTPase signaling pathways to the cytoskeleton through a multiprotein assembly called Arp2/3 complex. The C-terminal VCA regions (verprolin-homology, central hydrophobic, and acidic regions) of WASP and its relatives stimulate Arp2/3 complex to nucleate actin filament branches. Here we show by differential line broadening in NMR spectra that the C (central) and A (acidic) segments of VCA domains from WASP, N-WASP and Scar bind Arp2/3 complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
141
2
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(155 citation statements)
references
References 43 publications
10
141
2
2
Order By: Relevance
“…A combination of TROSY pulse sequences, 100% deuteration, buffer optimization (23), and use of a cryoprobe enabled us to acquire high quality NOESY spectra at protein concentrations of 150 -400 M. From the observed NOEs we determined direct connectivity of a number of residues. Consistent with previous reports (7,24), our data indicate that the VC domain by itself is unfolded and that about 40% of the VC peptide adopts a helical conformation upon binding actin.…”
Section: Secondary Structure and Interacting Residues Of The Vc-actinsupporting
confidence: 81%
“…A combination of TROSY pulse sequences, 100% deuteration, buffer optimization (23), and use of a cryoprobe enabled us to acquire high quality NOESY spectra at protein concentrations of 150 -400 M. From the observed NOEs we determined direct connectivity of a number of residues. Consistent with previous reports (7,24), our data indicate that the VC domain by itself is unfolded and that about 40% of the VC peptide adopts a helical conformation upon binding actin.…”
Section: Secondary Structure and Interacting Residues Of The Vc-actinsupporting
confidence: 81%
“…Therefore, a path along the actin nucleotide cleft is not necessary for nucleotide exchange inhibition, suggesting that this function resides within the N-terminal part of WH2 and T␤. In agreement with this notion, WIP [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] , corresponding to the N-terminal ␣-helix, inhibits nucleotide exchange as potently as the full-length WH2 motif after taking into consideration the lower actin-binding affinity of this peptide. Therefore, we conclude that nucleotide exchange inhibition is a function of the N-terminal ␣-helix of WH2 and T␤, which binds between actin subdomains 1 and 3, away from the nucleotide site.…”
Section: Control Of Actin Nucleotide Exchange By Wh2 and T␤supporting
confidence: 48%
“…This conclusion is further supported by the fact that T␤4 , starting from the LKKT sequence to the end, fails to bind actin. Similarly, the N-terminal portion of WIP (WIP [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] ) accounts for most of its binding affinity, whereas WIP 46-63 binds very weakly. Therefore, it can be concluded that hydrophobic contacts involving the N-terminal ␣-helices of WH2 and T␤ play a predominant role in the interaction with actin over electrostatic interactions within their C-terminal portions.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of GFP-A inhibited HIV-1 infection less efficiently than other derivatives (57.7%, p Ͻ 0.05; Figure 4C). However, GFP-A was unable to limit IMV infection (110.8%, Figure 4C) although synthetic peptides of A subdomain has been shown to retain the binding affinity to the Arp2/3 complex as high as VCA in vitro (Panchal et al, 2003). These data suggested that the V subdomain was not required for the inhibition of HIV-1 and IMV infection.…”
Section: Gfp-vca's Ability To Nucleate Actin Filament Is Not Necessarmentioning
confidence: 52%